Determination of Variation in Soil Water Storage Capacity on Watersheds - Kadri Yürekli (Journal of Agricultural Sciences)
The purpose ofthis study is to bring up variation of soil water storage capacity (S) based on probability distributions on vvatersheds, and to compare S obtained from probability distribution to S according to Soil Conservation Service (SCS). İn order to explaining variation in S, maximum 24-h rainfall for each month ana the associated runoff volüme recorded in three vvatersheds ( Uğrak, Akdoğan, Ikikara) vvhich has controlled by Tokat Research Institute of Rural Services was used. Normal, log normal, extreme value type I, and log pearson type III distributions were taken into account for S in this study. S values of these mentioned vvatersheds vvere fıtted better to log normal distribution than the others (normal, extreme value type I, and log pearson type III distributions ). S values of each vvatersheds for 10, 50 and 90 % probability levels vvere götten from freçuency lines based on log normal distribution. Aftervvards, for these S values, curve numbers (CN)0, CN50, CN90) vvere determined. These CN values vvere compared to CN values (CN,, CN„, CN,,,) based on SCS for dry antecedent condition, normal antecedent condition, and wet antecedent condition. This study was shovved that CN,0, CN50. CNM vvere similar to CN,, CN„, CN,,, for each vvatershed (Uğrak, Akdoğan, Ikikara).